PERISTIWA BERDARAH SIANTAR HOTEL 15 OKTOBER 1945 - Putri Lestari; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to find out the background of the October 15 hotel event. But at this time many people did not know the events of the Siantar Hotel. This is due to a lack of curiosity about History in its own area. This study uses field research methods and literature studies to support informant data. With the type of qualitative descriptive research. The research was carried out in West Siantar Subdistrict, Pematang Siantar Municipality, with research informants, namely West Siantar people who were over 50 years old. Data collection techniques in this study are techniques through interviews and field observations. In this study it can be concluded that the Eruption of the Siantar Hotel Event on October 15, 1945, was motivated by a flag incident in the Siantar Hotel which turned out to disturb the Pematang Siantar Youth. Where the Netherlands / NICA tries to raise its three-color flag and is added with arrogant and arrogant actions and behavior displayed by Dutch / NICA soldiers to the people of Indonesia or the people of Siantar which of course will provoke the emotions of the people who have long been hidden to reciprocate. The Siantar Hotel event on October 15, 1945 pioneered the breadth of the Indonesian Proclamation of Independence in Pematang Siantar and Simalungun, where after the hotel siantar the young men were more courageous to oppose the Netherlands / NICA or more enthusiastic in fighting for Independence and more earnestly in defending Independence. owned or felt by Indonesia in general and Pematang Siantar in particular. So the Siantar Hotel event on October 15, 1945 gave a huge influence in the struggle for Indonesian Independence. Key Words: Event, Bloody,Siantar,October 15, 1945